Pemenuhan Hak dan Tanggung Jawab Suami terhadap Istri dengan Gangguan Kejiwaan: Analisis Sosio-Legal Berbasis Keadilan Gender di Jenggot, Pekalongan - Fitriyani, Fenti (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This research is based on the social reality that many husbands do not yet understand their responsibilities towards wives with mental disorders, even though the wife's psychological condition often affects family function, especially in emotional relationships and role distribution, so that husbands should continue to provide protection, affection, and fulfill physical and spiritual needs. Field facts show that most husbands do not fulfill their obligations optimally, even in some cases there is neglect, resulting in relationship inequality and gender injustice in the household. This study aims to identify the forms of fulfillment of rights and responsibilities of husbands towards wives with mental disorders, factors that influence these relationships, and review their implementation from a gender justice perspective. The research method used is qualitative with a juridical-sociological approach through interviews with husbands, families, religious leaders, and village officials, as well as a library study of Islamic law literature and gender justice theory. The analysis is conducted descriptively-analytical by comparing empirical findings and Islamic legal norms regarding the rights and obligations of husbands and wives. The results of the study show that the fulfillment of wives' rights is not met emotionally or economically, because the dominant decision-making is still in the hands of the husband, so it is necessary to increase the husband's awareness in order to create fair household relations according to Islamic teachings.